Association of alpha-1-adrenergic antagonist use with the risk of gout development in benign prostatic hyperplasia patients: a population-based cohort study. (29th December 2021) - Hsu, Wei-Hung; Lai, Jung-Nien; Lin, Cheng-Li; Loh, Ching-Hui; Huang, Huei-Kai; Huang, Liang-Kai
Abstract: Background: Men are more likely to develop benign prostatic hyperplasia (BPH) and gout as they age. However, the role of alpha-1-adrenergic antagonists, the medication for BPH, in the development of gout is uncertain. Objective: To investigate the effect of alpha-1-adrenergic antagonist use on the risk of developing gout in BPH patients. Methods: Data of patients with newly diagnosed BPH were retrieved from Taiwan's 2000–2013 National Health Insurance Research Database (total number: 15, 390 patients; 7, 695 patients in each cohort). Propensity score matching was conducted according to age, comorbidities, medication history for cohorts that received or did not receive alpha-1-adrenergic antagonists. Hazard ratios (HRs) were assessed for gout development using Cox proportional hazards regression models. Results: Use of alpha-1-adrenergic antagonists was not associated with gout development in BPH patients (HR = 0.92; 95% confidence interval [CI], 0.78–1.10; P = 0.35). However, after stratification according to the average number of days of alpha-1-adrenergic antagonist use per year, patients with an average of >300 days had a significantly higher risk of gout development than patients who did not receive alpha-1-adrenergic antagonists (adjusted HR = 1.57; 95% CI, 1.25–1.97; P < 0.001). Patients with more days of medication use per year had a higher risk of gout development than those with fewer days of medication use ( P < 0.001). Conclusion: Patients who received more doses of alpha-1-adrenergic antagonists per year had a higher risk of developing gout. A causal proof of the role of alpha-1-adrenergic antagonists use in gout development should be analysed in future studies designed as double blind randomized controlled trials.